Mechanosensitive ion channels in the freshwater snail, Lymnaea stagnalis. - Sigurdson, Wade Johannes. (University of Ottawa (Canada), 1990)
Mechano-sensitive ion channels in cells isolated from the heart and circumoesophageal ganglia of a freshwater snail (Lymnaea stagnalis) were characterized as K$\sp+$ selective and sensitive to changes in cell membrane tension. Using the technique of single-channel recording, stretch-activated K$\sp+$ (SAK) channels (30 pS in physiological saline) were shown to have complex permeation properties indicative of multi-ion channels. SAK channels were blocked by milli-molar quantities of quinidine or tetraethyl-ammonium and exhibited selectivity (Tl$\sp+ >$ K$\sp+ >$ Rb$\sp+ >$ Na$\sp+ >$ Li$\sp+$) properties seen in many other K$\sp+$ channels. SAK channels described in Lymnaea ventricular cells or neuron somas and growth cones were activated (increased open probability, P$\sb{\rm o}$) by increases in membrane tension produced by suction on the cell membrane. Stretch-activation was a reversible and repeatable phenomenon, associated with a reduction in a long closed time separating bursts of openings, rather than by an increase in the open time. The SAK channel's stretch-sensitivity was variable between patches, a finding attributable to the inability to accurately determine membrane tension. In spite of this, kinetic analysis of heart SAK channels established the presence of at least two open and three closed states. Similar analysis of neuron SAK channels indicated at least two open and four closed states. In channels from both cell types, only the long closed time constant ($\tau\sb{\rm C4}$, extracted from closed time frequency distributions) showed sufficient mechano-sensitivity to produce the observed increase in P$\sb{\rm o}$ with increasing membrane tension (in one patch, when P$\sb{\rm o}$ increased by a factor of 77 times the zero pressure P$\sb{\rm o}$, $\tau\sb{\rm C4}$ decreased by a factor of 22). In spite of the absence of specific SAK channel antagonists, attempts were made to establish a physiological role for SAK channels. Neurons and heart cells were shown to be resistant to severe hyposmotic insults. Hyposmotic shock resulted in hyperpolarization of the neuron soma resting potential and activation of SAK channels. These results suggested that SAK channels may contribute to osmotic-swelling limitation. SAK channels were found in developing neuron growth cones as well as the cell body. Channel characteristics were similar in both structures and circumstantial evidence points to expression of new SAK channels during neurite development. A new type of mechano-sensitive K$\sp+$ channel was found to coexist with SAK channels in neuron cell bodies and growth cones. These channels were in-activated (SIK) by increases in membrane tension and possessed a greater stretch-sensitivity than SAK channels. Decreased P$\sb{\rm o}$ was found to result from the lengthening of the long closed time in a fashion analogous but opposite to that seen in SAK channels, thus implying a common transduction mechanism. The differing stretch-sensitivities combined with similar permeation properties (6.6 pS in physiological saline; selectivity sequence, Tl$\sp+ >$ K$\sp+ >$ Rb$\sp+ >$ Na$\sp+$) suggested that membrane tension could control cell resting potential and thus modulate voltage-activated Ca$\sp{2+}$ channels and therefore the influx of Ca$\sp{2+}$, a known regulatory ion. SIK and SAK channels could therefore provide a mechanism for linking Ca$\sp{2+}$ influx to tension during axonal outgrowth.
Keywords: Biology, Cell.